PENGARUH KEMANDIRIAN, LINGKUNGAN, DAN KESEJAHTERAAN TERHADAP ETOS KERJA KARYAWAN PT. TIRTA INVESTAMA DI KLATEN - ., Tunjungsari (-)
The Intentions of this research are: (1) To know the influence which signifikan from independence, environmental and prosperity of either through individually and also by together to ethos work the employees PT. Tirta Investama in Klaten. (2) To know among independence factor, environmental and prosperity owning dominant influence to work the. Benefit able to be taken away from this research is to be knowable how big independence influence, environmental and prosperity owning dominant influence to ethos work, so that can be conducted by effort ofis make-up of independence work the employees, environmental of good activity and prosperity more mounting to increase ethos work the employees. Hypothesis raised is: (1) Anticipated a independence, environmental and prosperity have an effect on positive and signifikan to ethos work the employees PT. Tirta Investama in Klaten. (2) Anticipated by a prosperity factor have the dominant influence to ethos work the PT. Tirta Investama in Klaten. This Research represents the descriptive research of type survey depicting phenomenon that happened at obyek research of there. Population in this research is all employees PT. Tirta Investama in Klaten amounting to 315 people and without entangling employees mount the superintendent and manager. Sampel in this research is 80 employees of part of production PT. Tirta Investama in Klaten taken with the technique of purposive random sampling. Technique of data collecting by kuesioner and documentation. Data collected by in the form of data of primary and data skunder. Method analyse the data use the double analysis regresi, test the F, test the t, and coefficient determinasi.